What is DAM - the discipline and practice of Digital Asset Management - Lipsey, David H. (Henry Stewart Talks, 2010)
Various forms of digital assets, Different kinds of information and storage options, Evolution of note taking and reference material, A quick history of DAM, What DAM is not, DAM as a discipline, Organizational considerations in DAM, The unique challenges of rich media content, Content economics and monetization as a component of DAM, Cross-application knowledge as an emerging component of DAM, The master keys to watch for in DAM